(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The founding of the scout movement was not a coincidence, but rather a response to a need and necessity, and this led to its spread all over the world, although its founder did not intend to find a school or give a clearance for a curriculum, but he launched his idea within the framework of his time and the requirements of his society, and he is doing so He preceded his era in every sense of the word, as his visions exceeded his characteristics as a scout to the needs of the society that surrounds him, and therefore Baden-Powell chose forest life for his love of nature and the open, and for his belief in the benefit of living and being active in the open air, which is not an invitation to disorder and laziness, but rather an exercise process To learn about nature in matters of living, growth and construction within the social framework